Machine learning–based hybrid framework for weather-driven forewarning of major groundnut pests - P. Minruhi; P. Lavanya Kumari; Santosha Rathod; B. Ramana Murthy; K. Devaki; Kapil Choudhary; S. Vishnu Shankar; Prabhat Kumar (International Journal of Biometeorology, 2026)

A promising approach for improved citric acid production by Aspergillus niger with the assistance of cinnamaldehyde derivatives - Boomika Jayanna; Rohith Gattu; Neha Pandey; Praveena Bhatt; Bettadaiah B. Kempaiah; Pushpa S. Murthy; Suhas Ramesh (Food Chemistry, 2025)

Optimizing in vitro pollen viability and cryopreservation protocols across flower positions in pomegranate cultivars and wild genotypes - Prativa Sahu; B. N. S. Murthy; P. E. Rajasekharan; Pradeep Kumar Vishwakarma (Palynology, 2025)

FPGA Processing for m-Delta (ẟ) Decomposition of L1 SLC Images for a Potential Smart Small Satellite Based CP-SAR Mission for Earth Observations - D. V. N. S. N. Murthy; J. K. Kishore; K. Mruthyunjaya Reddy; Stutee Gupta; L. J. Vijayakumar; N. Aparna; H. S. V. Usha Sundari Ryali; P. V. Jayasri; B. K. S. V. L. Varaprasad (Journal of the Indian Society of Remote Sensing, 2025)

Influence of Fossil Fuels on Carbonaceous Aerosols: A Comparison among Urban Locations in India - Atar Singh Pipal; R. Latha; B. S. Murthy; A. S. Panicker (Aerosol Science and Engineering, 2025)

Recurrent Swarms of Planktonic Shrimp Luciferidae De Haan, 1849 (Order: Decapoda) in the Neritic Waters of Tamil Nadu, Southeast Coast of India - R. S. Sathishkumar; B. Charan Kumar; C. Muthukumar; N. Logesh; Sanitha K. Sivadas; K. Ramu; M. V. Ramana Murthy (Marine Ecology, 2024)
Luciferidae (Decapoda) are an important component of mesozooplankton in pelagic food webs. This study investigated the spatiotemporal distribution and frequency of Luciferidae swarms along the Tamil Nadu coast, as observed during coastal monitoring cruises conducted between 2019 and 2022. Data were collected on various hydrobiological factors, including surface water temperature, salinity, chlorophyll a , zooplankton biomass, and the abundance of other mesozooplankton (such as copepods, cladocerans, and others) across eight locations in the coastal waters of Tamil Nadu, India. Salinity values were generally low ( Belzebub hanseni Nobili, 1905, as the only organism responsible for swarm formation, with its occurrence peaking in January 2022. During this period, B. hanseni reached a maximum abundance of 3294 ind. m −3 for adults and 4056 ind. m −3 for larvae, together contributing approximately 27% of the total zooplankton abundance. Swarms of B. hanseni were observed a total of seven times over the course of the study, correlating with periods of low sea surface temperature and high food availability. Pearson's correlation analysis revealed a significant relationship between the abundance of copepods and B. hanseni ( r = 0.84; p B. hanseni in the nearshore waters of the Tamil Nadu coast is largely driven by food availability and optimal environmental conditions, including water temperature and monsoonal influences. The findings also suggest that geographical features, such as mangrove habitats, may contribute to the occurrence of B. hanseni swarms in this region.

Effects of Soil Application of Nanobiochar-Based Nitrogen and Potassium Fertilizers on the Growth and Yield of Groundnut (Arachis Hypogaea L.) - K. Nagaraju; T. N. V. K. V. Prasad; M. Sreenivasa Chari; Y. Reddi Ramu; B. Ramana Murthy; M. V. S. Naidu; G. P. Leelavathy; P. Ram Mohan; A. G. Damu; D. Gopal (Journal of Soil Science and Plant Nutrition, 2024)

Atmospheric gaseous mercury and associated health risk assessment in the economic capital of India - M. Nageswar Rao; R. Latha; K. Nikhil; B. S. Murthy (Environmental Monitoring and Assessment, 2024)

Black Carbon Characteristics over a Semi-urban Environment in the Garhwal Himalayas - A. S. Panicker; K. Sandeep; A. S. Gautam; S. Kumar; G. Beig; R. Latha; B. S. Murthy (Pure and Applied Geophysics, 2023)

Molecular diversity assessment among the pomegranate genotypes belonging to diverse genetic background using microsatellite markers - Nusrat Perveen; Sarvamangala S. Cholin; Kulapati Hipparagi; G. Prabhuling; B. N. S. Murthy; Dadapeer Peerjade (Acta Physiologiae Plantarum, 2023)

An intelligent optimized cyclone intensity prediction framework using satellite images - C. Kishor Kumar Reddy; P. R. Anisha; Marlia Mohd Hanafiah; Y. V. S. S. Pragathi; B. V. Ramana Murthy; R. Madana Mohana (Earth Science Informatics, 2023)

Five-Year Fine Particulate Matter Assessment over a Western Indian Megacity - Vrinda Anand; Nikhil Korhale; Abhilash S. Panicker; Gufran Beig; B. S. Murthy (Pure and Applied Geophysics, 2023)

Compendious Index for Drillability: a rapid tool to assess drill penetration rate and bit life for rock engineering applications - B. N. V. Siva Prasad; V. M. S. R. Murthy; Sripad R. Naik (Bulletin of Engineering Geology and the Environment, 2023)

Seismic energy prediction to optimize rock fragmentation: a modified approach - A. Agrawal; B. S. Choudhary; V. M. S. R. Murthy (International Journal of Environmental Science and Technology, 2022)

Festival Ushered Pollutants in Indian Metropolitan Cities: Resemblance, Variance, and Concerns - Latha R; Vrinda Anand; Nikhil Korhale; Pramod Kori; Murthy B S (Environmental Processes, 2022)

Seismic velocity imaging of the Kumaon–Garhwal Himalaya, India - Prantik Mandal; D. Srinagesh; R. Vijayaraghavan; G. Suresh; B. Naresh; P. Solomon Raju; Aarti Devi; K. Swathi; Dhiraj K. Singh; D. Srinivas; Satish Saha; M. Shekar; et al. (Natural Hazards, 2022)

Assessment of biogrowth assemblages with depth in a seawater intake system of a coastal power station - T. Subba Rao; P. S. Murthy; P. Veeramani; D. S. Narayanan; R. Ramesh; B. N. Jyothi; D. Muthukumaran; M. Murugesan; A. Vadivelan; G. Dharani; J. Santhanakumar; G. A. Ramadass (Biofouling, 2021)

Seasonal variation in photosynthetic rates and satellite-based GPP estimation over mangrove forest - N. Lele; M. K. Kripa; M. Panda; S. K. Das; A. Hari Nivas; N. Divakaran; S. Naik-Gaonkar; A. Sawant; A. K. Pattnaik; R. N. Samal; T. Thangaradjou; A. Saravanakumar; et al. (Environmental Monitoring and Assessment, 2021)

Correction to: Particulate Matter and Black Carbon in the Brahmaputra Valley of Northeast India: Observations and Model Simulation - B. S. Murthy; R. Latha; R. Srinivas; G. Beig (Pure and Applied Geophysics, 2020)

Particulate Matter and Black Carbon in the Brahmaputra Valley of Northeast India: Observations and Model Simulation - B. S. Murthy; R. Latha; R. Srinivas; G. Beig (Pure and Applied Geophysics, 2020)

Characteristics and Variability of Carbonaceous Aerosols over a Semi Urban Location in Garhwal Himalayas - K. Sandeep; R. S. Negi; A. S. Panicker; Alok Sagar Gautam; D. S. Bhist; G. Beig; B. S. Murthy; R. Latha; Santosh Singh; S. Das (Asia-Pacific Journal of Atmospheric Sciences, 2020)

Aerosol-induced perturbation of surface fluxes over different landscapes in a tropical region - R. Latha; B. S. Murthy; B. Vinayak (International Journal of Remote Sensing, 2019)

Estimates of Carbonaceous Aerosol Radiative Forcing over a Semiurban Environment in Garhwal Himalayas - A. S. Panicker; K. Sandeep; R. S. Negi; A. S. Gautam; D. S. Bisht; G. Beig; B. S. Murthy; R. Latha; Santosh Singh; S. Das (Pure and Applied Geophysics, 2019)

WRF simulation of a severe hailstorm over Baramati: a study into the space–time evolution - B. S. Murthy; R. Latha; H. Madhuparna (Meteorology and Atmospheric Physics, 2018)

Identification of new resistant sources for bacterial blight in pomegranate - B. Tanuja Priya; B. N. S. Murthy; C. Gopalakrishnan; Rashmi B. Artal; S. Jagannath (European Journal of Plant Pathology, 2016)

Identification of Potential Habitat Patches for Connectivity Using Weighted Linear Combination (WLC) and Integral Index of Connectivity (IIC) at East Godavari District, Andhra Pradesh, India - Shanthala Devi B. S; M. S. R Murthy; Debnath Bijan; C. S. Jha (Journal of the Indian Society of Remote Sensing, 2016)

Microwave-assisted synthesis and biological evaluation of carbazole-based chalcones, aurones and flavones - D. Ashok; S. Ravi; Arram Ganesh; B. Vijaya Lakshmi; Shaik Adam; S. D. S. Murthy (Medicinal Chemistry Research, 2016)

Taste Masking of Griseofulvin and Caffeine Anhydrous Using Kleptose Linecaps DE17 by Hot Melt Extrusion - Abhishek Juluri; Carmen Popescu; Leon Zhou; Reena N. Murthy; Vanaja K. Gowda; Chetan Kumar P; Manjeet B. Pimparade; Michael A. Repka; S. Narasimha Murthy (AAPS PharmSciTech, 2016)

Synthesis, X-ray characterization and biological evaluation of some new 2-(4-methy-2-oxo-2H-chromen-7yloxy) acetamide derivatives - Bhagavathula S. Diwakar; B. Govindh; Y. Nagendra Sastry; D. S. V. G. K. Kaladhar; Y. L. N. Murthy (Medicinal Chemistry Research, 2015)

A study on agricultural drought vulnerability at disaggregated level in a highly irrigated and intensely cropped state of India - C. S. Murthy; Manoj Yadav; J. Mohammed Ahamed; B. Laxman; R. Prawasi; M. V. R. Sesha Sai; R. S. Hooda (Environmental Monitoring and Assessment, 2015)

Synthesis and mosquito larvicidal activity of furanochalcones and furanoflavonoids analogous to karanjin - Susarla R. Satyavani; Sanjit Kanjilal; Muthineni S. Rao; Rachapudi B. N. Prasad; Upadyayula S. N. Murthy (Medicinal Chemistry Research, 2015)

Predictive models for pot-hole depth in underground coal mining—some Indian experiences - R. D. Lokhande; V. M. S. R. Murthy; K. B. Singh (Arabian Journal of Geosciences, 2014)

Response of Cassava canopy to mid-day pseudo sunrise induced by solar eclipse - R. Latha; B. S. Murthy (International Journal of Biometeorology, 2013)

Synthesis, antimicrobial and cytotoxic activities of novel 4-trifluoromethyl-(1,2,3)-thiadiazolo-5-carboxylic acid hydrazide Schiff’s bases - P. Sambasiva Rao; C. Kurumurthy; B. Veeraswamy; G. Santhosh kumar; B. Narsaiah; K. Pranay Kumar; U. S. N. Murthy; Santosh Karnewar; Srigiridhar Kotamraju (Medicinal Chemistry Research, 2013)

Pot-hole Subsidence in Underground Coal Mining: Some Indian Experiences - R. D. Lokhande; V. M. S. R. Murthy; K. B. Singh (Geotechnical and Geological Engineering, 2013)

Synthesis of novel optically pure α-amino acid functionalised-7-trifluoromethyl substituted quinolone derivatives and their antibacterial activity - B. P. Venkat Lingaiah; T. Yakaiah; A. Ravi Kumar; G. Sathaiah; A. Chandra Shekhar; K. Raju; P. Shanthan Rao; B. Narsaiah; U. S. N. Murthy (Medicinal Chemistry Research, 2013)

Effect of brewer’s yeast on immune response of giant freshwater prawn, Macrobrachium rosenbergii, and its resistance to white muscle disease - Prakash V. Parmar; H. Shivanada Murthy; C. S. Tejpal; B. T. Naveen Kumar (Aquaculture International, 2012)

Natural reduction of CO2 observed in the pre-monsoon period at the coastal station, Goa - R. Latha; B. S. Murthy (Meteorology and Atmospheric Physics, 2012)

Soret and Dufour effects on Double-Diffusive Free Convection From a Corrugated Vertical Surface in a Non-Darcy Porous Medium - B. V. Rathish Kumar; S. V. S. S. N. V. G. Krishna Murthy (Transport in Porous Media, 2010)

Geospatial modelling for identification of potential ecological corridors in Orissa - A. Roy; B. S. S. Devi; B. Debnath; M. S. R. Murthy (Journal of the Indian Society of Remote Sensing, 2010)

An Ex Vivo Toe Model Used to Assess Applicators for the Iontophoretic Ungual Delivery of Terbinafine - Anroop B. Nair; Hyun D. Kim; Shawn P. Davis; Robert Etheredge; Michael Barsness; Phillip M. Friden; S. Narasimha Murthy (Pharmaceutical Research, 2009)

In vitro germination and micropropagation of Givotia rottleriformis Griff. - K. Samuel; D. Debashish; B. Madhumita; G. Padmaja; Siva Ram Prasad; V. Bhaskara Ramana Murthy; P. S. Rao (In Vitro Cellular & Developmental Biology - Plant, 2009)

On the influence of spatial heterogeneity on an internal boundary layer at a short fetch - B. S. Murthy; R. Latha; Cini Sukumaran; A. Shivaji; S. Sivaramakrishnan (Journal of Earth System Science, 2009)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Active forest fire monitoring in Uttaranchal State, India using multi‐temporal DMSP‐OLS and MODIS data - T. R. Kiran Chand; K. V. S. Badarinath; M. S. R. Murthy; G. Rajshekhar; C. D. Elvidge; B. T. Tuttle (International Journal of Remote Sensing, 2007)

An Overview of the Land Surface Processes Experiment (Laspex) over a Semi-Arid Region of India - K. G. Vernekar; S. Sinha; L. K. Sadani; S. Sivaramakrishnan; S. S. Parasnis; Brij Mohan; S. Dharmaraj; M. N. Patil; J. S. Pillai; B. S. Murthy; S. B. Debaje; A. Bagavathsingh (Boundary-Layer Meteorology, 2003)

Observation of Double-mixing Line Structure in the Convective Boundary Layer During the Summer Monsoon Season - B. S. Murthy; S. S. Parasnis (Pure and Applied Geophysics, 2002)

Medicinal plants for treatment of diabetes mellitus - R. Shukia; S. B. Sharma; D. Puri; K. M. Prabhu; P. S. Murthy (Indian Journal of Clinical Biochemistry, 2000)

Structure of the Lower Crust Revealed by One- and Two-dimensional Modeling of Wide-angle Reflections -- West Bengal Basin, India - I. B. P. Rao; P. R. K. Murthy; P. Koteswara Rao; A. S. N. Murty; N. Madhava Rao; K. L. Kaila (Pure and Applied Geophysics, 1999)

Characterization of somatic embryogenesis in Pelargonium ×× hortorum mediated by a bacterium - B. N. S. Murthy; N. N. Vettakkorumakankav; S. KrishnaRaj; J. Odumeru; P. K. Saxena (Plant Cell Reports, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Wavelet Analysis of Intermittent Turbulent Transport in the Atmospheric Surface Layer over a Monsoon Trough Region - J. R. Kulkarni; L. K. Sadani; B. S. Murthy (Boundary-Layer Meteorology, 1999)

Thidiazuron: A potent regulator ofin vitro plant morphogenesis - B. N. S. Murthy; S. J. Murch; Praveen K. Saxena (In Vitro Cellular & Developmental Biology - Plant, 1998)

Somatic embryogenesis and plant regeneration of neem ( Azadirachta indica A. Juss.) - B. N. S. Murthy; Praveen K. Saxena (Plant Cell Reports, 1998)

Studies on Degradation of 14 C-Nitrofen in Soils Under Moist and Flooded Conditions Using a Continuous Flow System in the Laboratory - S. P. Kale; N. B. K. Murthy; K. Raghu (Bulletin of Environmental Contamination and Toxicology, 1997)

Cattle mortality in the Thane district, India: A study of cause/effect relationships - R. K. S. Dogra; R. C. Murthy; A. K. Srivastava; J. S. Gaur; L. J. Shukla; B. M. L. Varmani (Archives of Environmental Contamination and Toxicology, 1996)

Cattle Mortality in the Thane District, India: A Study of Cause/Effect Relationships - R. K. S. Dogra; R. C. Murthy; A. K. Srivastava; J. S. Gaur; L. J. Shukla; B. M. L. Varmani (Archives of Environmental Contamination and Toxicology, 1996)